Secular societies, spiritual selves?
1 online resource (xiv, 240 pages)
Keywords: "Secular Societies, Spiritual Selves brings together ethnographic research to address how the overlaps and differentiations between spirituality, secularity and religion are gendered. The book examines how 'spirituality' has emerged as a relatively 'silent' category with which people signal that they are looking for a way to navigate between the categories of the religious and the secular, and considers how this is related to, explicitly or implicitly, gendered ways of being and self-constitution. The contributors discuss the intersections between spirituality, religion and secularism in different geographical areas, ranging from the Netherlands, Portugal and Lithuania to Canada, the United States and Mexico. Exploring the spiritual experiences of women and their struggle for a more gender equal way of approaching the divine, the chapters also examine the experience of men and of those who challenge binary sexual identities advocating for a queer spirituality. This volume will be of interest to scholars of the anthropology and sociology of religion as well as religious studies and gender studies"--